Agro-biodiversity Management: An Opportunity for Mainstreaming Community-based Adaptation to Climate Change (Journal of Forest and Livelihood, 2009)
Climate risks and hazards adversely impact the livelihoods of local communities. Based on a recent participatory study conducted in the western hills of Nepal, this article explores opportunities and strategies for integrating climate change adaptation in poverty reduction projects and programmes in ways that increase the capacity of individuals, households and communities to respond to climate variability and change. The findings of the study suggest that a wide array of agro?-biodiversity management strategies offer options and opportunities for farmers to cope with the adverse impact of climate change. However, this is possible only if adaptation is incorporated into the existing development efforts with sufficient understanding of local livelihood context and strategies instead of separately planning climate change adaptation programmes.Key words: Climate risks and hazards, community-based adaptation, vulnerability, poor, farmers, agriculture  Full text is available at the ForestAction websiteJournal of Forest and Livelihood 8(1) February 2009 pp.111-119